(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
A simple, rapid, and sensitive method based on liquid chromatography-tandem mass spectrometry for the quantitative determination of simvastatin in human plasma was developed and validated. After a simple extraction with methyl tert-butyl ether, the analyte and internal standard (lovastatin) were analyzed using reverse-phase liquid chromatography, on a Kinetex C18 column (100 × 4.6 mm, 2.6 μm) using acetonitrile: ammonium acetate (2 mM + 0.025 % formic acid) (70: 30, v/v) as a mobile phase in a run time of 3.5 min. Detection was carried out using electrospray positive ionization mass spectrometry in the multiple-reaction monitoring mode. The method was linear over 0.04-40.0 ng/mL concentration range. The mean extraction recovery of simvastatin was 82% (RSD within 15%). Intraday and interday precisions (as relative standard deviation) were all ≤8,7% with accuracy (as relative error) of ±8%. This rapid and reliable method was successfully applied for a bioequivalence study of 40 mg of simvastatin orally disintegrating tablets in 44 healthy volunteers, showing that this method is suitable for the quantification of simvastatin in human plasma samples for pharmacokinetics and bioequivalence studies.